Social Positions and Fairness Views on Inequality - Hvidberg, Kristoffer B; Kreiner, Claus T; Stantcheva, Stefanie (Review of Economic Studies, 2023)
Abstract We link survey data on Danish people’s perceived income positions and fairness views on inequality within various reference groups to administrative records on their reference groups, income histories, and life events. People are, on average, well-informed about the income levels of their reference groups. Yet, lower-ranked respondents in all groups tend to overestimate their own position among others because they believe others’ incomes are lower than they actually are, whereas the opposite holds true for higher-ranked respondents. Misperceptions of positions in reference groups relate to proximity to other individuals, transparency norms, and visible signals of income. People view inequalities within their co-workers and education groups as significantly more unfair than overall inequality, yet underestimate inequality the most exactly within these groups. Views on the fairness of inequalities are strongly correlated with an individual’s current position, move with shocks like unemployment or promotions, and change when experimentally informing people about their actual positions. However, the higher perceived unfairness of income differences within co-workers and education groups stays unchanged. The theoretical framework shows that this can have important implications for redistribution policy.